Memaknai Delik Dan Delik Tata Negara - sarip sarip sarip (DE LEGA LATA: JURNAL ILMU HUKUM, 2019)
The term delik is still identified with criminal law, the offense itself comes from delict in various legal literatures. That according to the positive law a strafbaar feit is actually nothing other than an action which according to a formulation of the law has been declared a punitive action. The thought that was considered wrong in learning stated that the term delict was criminal. The wrong terminology eventually spread among the students who always named delict as a criminal. Research on interpreting delicts and state administration offenses is a study carried out using old literature. Old literature has been chosen to strengthen the argument in finding a bright spot about the meaning of the offense itself. Writing defines offenses and constitutional offenses including in normative legal research carried out through various efforts to thoroughly examine and analyze legal provisions relating to research problems (study of law in the book). Through the meaning in the discussion it was found that the meaning of offense is basically not limited to criminal matters but can also be used in the meaning of state administration. So in constitutional offenses, an offense is used to gain power or maintain power. In addition, state administration offenses cannot be separated from the sovereignty theory itself. Then it can be concluded that the meaning of offense at this time is only trapped in a criminal that actually has a neutral meaning that is not limited to criminal matters.